BGer 4P.216/2006 vom 21. November 2006 - Bundesgericht (2006)
art. 6 par. 1 CEDH; art. 5 al. 1, 9, 29, 30, 36 al. 1 Cst.; principe de la légalité, déni de justice formel, arbitraire | Procédure civile